2013
DOI: 10.5539/par.v2n2p49
|View full text |Cite
|
Sign up to set email alerts
|

Procurement Reforms in Africa: The Strides, Challenges, and Improvement Opportunities

Abstract: Procurement reforms are seen as essential for achieving a long term improvement in financial management within Africa. To gain insight into this situation an analysis of success stories and cases where challenges and difficulties have arisen were investigated. This material was content analysed using Mayring (2008) four-step process model. The findings demonstrate some initial improvement within African public sector financial management; however the complete and successful implementation of these reforms is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…A broader review of literature also reveals numerous potential factors that account for the non-achievement of VfM in public projects. For instance, Dza et al (2013) reported the lack of consideration of VfM in public contracts, Barr and Christie (2015) indicated the lack of methodological guidance for achieving VfM, Jackson, (2012) identified the lack of data for VfM assessment and Wu et al (2008) reported the issue of governments initiating projects without sufficient funding arrangements. Also, poor procurement strategies (World Bank, 2016), contracts subjected to delays (Crown Agents, 1998), mismanagement of funds by responsible agencies (Audit Service of Ghana, 2017, 2016), the manipulation of VfM assessment results to post justify already decided projects (Europe PPP Expertise Centre, 2015), lack of incentives in government contracts (Hughes et al , 2007), the effect of poor stakeholder engagement (Ankukumah, 2017) and the impact of some macroeconomic variables (inflation, interest rate and exchange rate) on construction projects (Oladipo and Oni, 2012) are some factors that account for the non-achievement of VfM in construction projects.…”
Section: Concept Of Value For Moneymentioning
confidence: 99%
“…A broader review of literature also reveals numerous potential factors that account for the non-achievement of VfM in public projects. For instance, Dza et al (2013) reported the lack of consideration of VfM in public contracts, Barr and Christie (2015) indicated the lack of methodological guidance for achieving VfM, Jackson, (2012) identified the lack of data for VfM assessment and Wu et al (2008) reported the issue of governments initiating projects without sufficient funding arrangements. Also, poor procurement strategies (World Bank, 2016), contracts subjected to delays (Crown Agents, 1998), mismanagement of funds by responsible agencies (Audit Service of Ghana, 2017, 2016), the manipulation of VfM assessment results to post justify already decided projects (Europe PPP Expertise Centre, 2015), lack of incentives in government contracts (Hughes et al , 2007), the effect of poor stakeholder engagement (Ankukumah, 2017) and the impact of some macroeconomic variables (inflation, interest rate and exchange rate) on construction projects (Oladipo and Oni, 2012) are some factors that account for the non-achievement of VfM in construction projects.…”
Section: Concept Of Value For Moneymentioning
confidence: 99%
“…The public finance (Tender Board) regulations of 1977 were passed under the 1964 Public Finance Act, which replaced the colonial system where public procurement for most government entities was conducted through a central tender board (Dza et al, 2013;Khi V. Thai, 2009;Sabiiti and Muhumuza, 2012). However, the promulgation of a new constitution in 1995 expanded the size of government:…”
Section: Development Partnersmentioning
confidence: 99%
“…Based on Tanayut C., Narong L., Preenithi A. & Patrick M. (2017) [14]., it was found that some government officials were purposely dishonest in seeking benefits from the procurement process, which included violating, distorting, or avoiding regulations and/or laws [15].…”
Section: Government Procurement Problemsmentioning
confidence: 99%